2020
DOI: 10.1142/s0218301320300040
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical progress on production of isotopes in the multinucleon transfer process

Abstract: As one promising approach for producing nuclei beyond the [Formula: see text]-stability line, the multinucleon transfer (MNT) process has been extensively investigated in past decades. An overview of the theoretical progress on production of isotopes in MNT process is presented. The dinuclear system model, one hybrid approach (GRAZING+DNS model), the improved quantum molecule dynamic model, and the model based on the Langevin equations are summarized. The nucleon transfer mechanisms, such as effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 156 publications
0
1
0
Order By: Relevance
“…The aim of the present article is to predict the synthesis of more neutron-rich Lr isotopes within 249 Bk and 254 Es targets under the framework of the DNS model. Recent research progress of DNS model about MNT reactions can be found in the review references [100][101][102].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present article is to predict the synthesis of more neutron-rich Lr isotopes within 249 Bk and 254 Es targets under the framework of the DNS model. Recent research progress of DNS model about MNT reactions can be found in the review references [100][101][102].…”
Section: Introductionmentioning
confidence: 99%